Tanggung Jawab Pendidik Dan Implikasinya Terhadap Lingkungan Pendidikan Islam - Mumu Zainal mutaqin; Nurwadjah Ahmad; Andewi Suhartini (Universitas Cokroaminoto Yogyakarta, 2021)
Responsibility is a job to perform an obligation or complete a task with full satisfaction given by someone on his own promise or commitment. Educators are not just teachers, but the creation of adequate quality education includes parents, teachers and the community. The research aims to raise human awareness of intentional and unintentional behavior and actions. the responsibility of educators is the obligation to bear, maintain and provide training in the form of teaching about morals and intelligence of the mind. An educator has a responsibility for students who are under the auspices of his leadership how to direct them towards maturity, both intellectually, mentally and morally, to carry out the humanitarian function they carry. as a servant before his Khaliq and also as Khalifatu fil ardh (maintainer) in this universe.